Trypanorhynch cestodes (Eutetrarhynchidae) from batoids along the coast of Argentina, including the description of new species in Dollfusiella Campbell et Beveridge, 1994 and Mecistobothrium Heinz et Dailey, 1974 - Menoret, Adriana (2015)
During a recent parasitological survey of elasmobranchs along the coast of Argentina, two new species of eutetrarhynchid cestodes of the genera Dollfusiella Campbell et Beveridge, 1994 and Mecistobothrium Heinz et Dailey, 1974 were collected from batoids. Dollfusiella acuta sp. n. was found in four arhynchobatid skates, i.e. Sympterygia acuta Garman (type host), Sympterygia bonapartii Müller et Henle, Atlantoraja castelnaui (Miranda Ribeiro) and Atlantoraja platana (Günther), and Mecistobothrium oblongum sp. n. in the eagle ray Myliobatis goodei Garman. Dollfusiella acuta sp. n. has a tentacular armature consisting of basal rows of uncinate hooks, a distinct basal swelling with uncinate, falcate and bill hooks, and a heteroacanthous metabasal armature with heteromorphous hooks (bothrial uncinate hooks and antibothrial falcate hooks), hooks 1(1') not separated, testes in two columns and an internal seminal vesicle. The tentacular armature of M. oblongum sp. n. is characterised by basal rows of uncinate hooks, a basal swelling with uncinate and falcate hooks, a typical heteroacanthous metabasal armature with heteromorphous hooks (uncinate and falcate to spiniform), and hooks 1(1') separated and of a constant size along the tentacle. It also possesses an elongate scolex, numerous testes arranged in 5-6 irregular columns, and an internal seminal vesicle. The discovery of M. oblongum in M. goodei represents the first record of species of Mecistobothrium in the southwestern Atlantic Ocean. An amended description of Dollfusiella cortezensis (Friggens et Duszynski, 2005) is also provided to clarify details of the scolex and tentacular armature. Members of Dollfusiella in the southwestern Atlantic are specific to a single host species or to a particular host family, while M. oblongum was found in a single host species. Although globally some plerocerci of eutetrarhynchids have been found in teleosts, extensive examination of teleosts off the coast of Argentina suggests that the transmission pathways of these species are exclusively based on invertebrates as intermediate or paratenic hosts.